PERAN ISLAMIC HYPNO PARENTING MELALUI METODE DEEP TALK TERHADAP PERKEMBANGAN KECERDASAN SOSIAL EMOSIONAL ANAK : (Studi Kasus Pada Orang Tua yang Menggunakan Islamic Hypno Parenting di Desa Sitanggal Kecamatan Larangan Kabupaten Brebes) - Ta'ti Mamlakah; Muslihudin Muslihudin; Cecep Sumarna (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Parental parenting styles have a very important role in children's development, but wrong parenting styles will have a negative impact on children's development and vice versa. Early childhood children usually cannot control their emotions, they will get angry easily, cry, be stubborn, scream, and sometimes even become violent. This research aims to determine 1) The application of Islamic hypno parenting through the deep talk method in early childhood in Sitangan Village, Larangan District, Brebes Regency, 2) The development of social emotional intelligence in early childhood in Sidate Village, 3) The impact of Islamic hypno parenting through the deep method talk on the development of social emotional intelligence of early childhood in Sitangan Village. The method used in this research is descriptive qualitative. The data collection techniques used in this research are observation, interviews and documentation. Based on the research that has been carried out, there are results: 1) Islamic hypno parenting can be applied to young children in Sitangan Village through the deep talk method, by giving suggestions in the form of stories, stories and repeated words, after which the parents will give deep talk in the form of questions related to stories, narratives and expressions. 2) The development of social emotional intelligence in early childhood in Sitangan Village is influenced by parenting patterns from parents and the environment. Social emotional intelligence can be developed through interaction between parents and children, as well as habits made by parents towards their children. 3) There are several impacts from implementing Islamic hypno parenting through the deep talk method, namely increasing children's emotional development, fostering empathy, strengthening Islamic religious values, strengthening the relationship between parents and children, as well as openness between parents and children.